Biased Agonism at G Protein‐Coupled Receptors: The Promise and the Challenges—A Medicinal Chemistry Perspective. Issue 6 (5th May 2014) - Shonberg, Jeremy; Lopez, Laura; Scammells, Peter J.; Christopoulos, Arthur; Capuano, Ben; Lane, J. Robert
Abstract Historically, determination of G protein‐coupled receptor (GPCR) ligand efficacy has often been restricted to identifying the ligand as an agonist or antagonist at a given signaling pathway. This classification was deemed sufficient to predict compound efficacy at all signaling endpoints, including the therapeutically relevant one(s). However, it is now apparent that ligands acting at the same GPCR can stabilize multiple, distinct, receptor conformations linked to different functional outcomes. This phenomenon, known as biased agonism, stimulus bias, or functional selectivity offers the opportunity to separate on‐target therapeutic effects from side effects through the design of drugs that show pathway selectivity. However, the medicinal chemist faces numerous challenges to develop biased ligands, including the detection and quantification of biased agonism. This review summarizes the current state of the field of research into biased agonism at GPCRs, with a particular focus on efforts to relate biased agonism to ligand structure.